Relationships between functional alpha and beta diversities of flea parasites and their small mammalian hosts - Krasnov, Boris R. (2024)
We studied the relationships between functional alpha and beta diversities of fleas and their small mammalian hosts in four biogeographic realms (the Afrotropics, the Nearctic, the Neotropics, and the Palearctic), considering three components of alpha diversity (functional richness, divergence, and regularity). We asked whether (a) flea alpha and beta diversities are driven by host alpha and beta diversities; (b) the variation in the off-host environment affects variation in flea alpha and beta diversities; and (c) the pattern of the relationship between flea and host alpha or beta diversities differs between geographic realms. We analysed alpha diversity using modified phylogenetic generalised least squares and beta diversity using modified phylogenetic generalised dissimilarity modelling. In all realms, flea functional richness and regularity increased with an increase in host functional richness and regularity, respectively, whereas flea functional divergence correlated positively with host functional divergence in the Nearctic only. Environmental effects on the components of flea alpha diversity were found only in the Holarctic realms. Host functional beta diversity was invariantly the best predictor of flea functional beta diversity in all realms, whereas the effects of environmental variables on flea functional beta diversity were much weaker and differed between realms. We conclude that flea functional diversity is mostly driven by host functional diversity, whereas the environmental effects on flea functional diversity vary (a) geographically and (b) between components of functional alpha diversity.